Counseling Adolescents About the Intrauterine Contraceptive Device - Susan E. Rubin; Hillel W. Cohen; John S. Santelli; M. Diane McKee (SAGE Publishing, 2015)
Background: The intrauterine device (IUD) is a highly effective contraceptive, yet not all primary care providers (PCPs) counsel adolescents about IUDs. We sought to describe PCPs' frequency of counseling adolescents about IUDs and identify whether different factors are associated with frequent counseling by pediatricians compared with family physicians and gynecologists. Methods: Surveyed PCPs affiliated with a Bronx, New York academic institution. Main Outcome: Frequent counseling of female adolescents about IUDs. Results: Frequent counseling was lower in pediatricians compared with family physicians and gynecologists (35.8% and 81.6%, respectively, P < .001). Among all PCP types, frequent counseling was associated with feeling more competent counseling and managing expected IUD side effects ( P < .001). Other significant variables included inserting IUDs themselves ( P < .001, family physicians and gynecologists) or having access to an inserter in their office ( P = .04, pediatricians). Conclusions: Correlates of frequent IUD counseling differed according to PCP specialty. Our results suggest that interventions to increase IUD counseling should focus on improving PCPs' competency around counseling and side effect management as well as increasing access to IUD inserters.